C++ programming fundamentals - Easttom, Chuck (Hingham, Mass. : Charles River Media, 2003)
Introduces basic concepts of C++ programming, including Microsoft Vi sual C++, using examples from such areas as game programming and GPA ca lculation, and provides fully functional sample programs.
Keywords: C++ (Computer program language) -- Juvenile literature; C++ (Computer program language).; Programming (Computers).; Computers